PENANAMAN NILAI-NILAI PENDIDIKAN KARAKTER SISWA MELALUI BUDAYA DISIPLIN DI SEKOLAH DASAR - Erlin Anjelina Tunga Wea; Andriani Mbagha; Maria Geovani Ngonu Laja; Maria Karolina Gare; Maria Desidaria Noge (STKIP Subang, 2025)
This study aims to explain how character education values can be instilled in students through the cultivation of discipline at Sekolah Dasar Impres (SDI) Tibakisa, located in Boawae District, Nagekeo Regency, East Nusa Tenggara. The cultivation of discipline is considered a crucial method for building students' character from an early age, particularly in instilling values such as responsibility, honesty, orderliness, and civility. The research employs a descriptive qualitative approach, using data collection techniques including observation, structured interviews, and document analysis.The findings of this study show that SDI Tibakisa has implemented a variety of disciplinary strategies, such as the 3S program (smile, greet, and say hello), morning assemblies, environmental cleanliness maintenance, enforcement of rules for both students and teachers, and the promotion of ethical habits in interactions among school members. The consistent application of these disciplinary measures has created a positive learning environment, supported students' character development, and fostered an orderly and supportive atmosphere However, there are still challenges faced, such as a lack of awareness about discipline among some students, limited support from families, and overly familiar relationships between students and teachers. Therefore, collaboration among the school, teachers, parents, and the community is necessary to ensure that character education can be implemented optimally and sustainably.